2013
DOI: 10.7314/apjcp.2013.14.12.7467
|View full text |Cite
|
Sign up to set email alerts
|

IL-6-6331 (T/C, rs10499563) is Associated with Decreased Risk of Gastric Cancer in Northern Chinese

Abstract: Background: Polymorphisms of genes encoding cytokines could be potential biomarkers to predict risk of gastric cancer (GC). Here, we investigated the association between the IL-6 -6331 (T/C, rs10499563) polymorphism in its promoter region and GC risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Interestingly, this finding could not be associated with Helicobacter pylori infection, implying that other cellular mechanisms could contribute to the increased susceptibility of A allele carriers for the development of intestinal type of GC. In another study, it has been shown that the TC or CC genotypes of IL‐6 rs10499563 were associated with a reduced risk of diffuse type GC [Yang et al, ]. In a study evaluating HMGB1 rs1045411, it was observed that AG/AA genotypes conferred more favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this finding could not be associated with Helicobacter pylori infection, implying that other cellular mechanisms could contribute to the increased susceptibility of A allele carriers for the development of intestinal type of GC. In another study, it has been shown that the TC or CC genotypes of IL‐6 rs10499563 were associated with a reduced risk of diffuse type GC [Yang et al, ]. In a study evaluating HMGB1 rs1045411, it was observed that AG/AA genotypes conferred more favorable prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic and environmental factors in addition to Helicobacter pylori infections have been identified to play important roles in the development of gastric cancer (Houghton and Wang, 2005;Merchant, 2005;Dong et al, 2008), the precise etiology of the disease remains unclear. Notably, more and more studies have indicated that genetic variants of interleukin (IL) family genes may be involved in the development of gastric cancer (El-Omar et al, 2000;Xue et al, 2012;Yang et al, 2013;Pan et al, 2014;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was stated that IL-6 rs10499563 was a functional polymorphism site in the promoter region of IL-6 and could transcriptionally regulate the expression of IL-6 [15]. Recently, several researchers found that IL-6 rs10499563 polymorphism was linked to gastric cancer risk [16,17]. However, the relationship of IL-6 rs10499563 and the progression of HBVrelated liver cirrhosis has not been studied.…”
Section: Discussionmentioning
confidence: 99%